ANALISIS STRATEGI PENINGKATAN PRODUKSI TAHU TEMPE DI DESA WEHALI KECAMATAN MALAKA TENGAH KABUPATEN MALAKA - Redjo , Paulina Rosna Dewi; Aksa, Adi Faisal; Ayuwinda Seran, Maria (Perwira Journal of Economics & Business, 2025)
Increasing tofu and tempeh production is an effort made to increase the quantity and quality of tofu and tempeh production. The aim of this research is to find out about the Strategy Analysis for Increasing Tofu and Tempe Production in Wehali Village, Central Malaka District, Malaka Regency using the Analytical Hierarchy Process (AHP) method with the criteria of Raw Materials, Labor, Capital. Data was collected from the opinions of respondents who are owners of the UD Mekar Sari and Abdi Jaya tofu and tempeh businesses in the form of a paired comparison questionnaire using the Saaty scale (1-9). Based on data processing using the AHP method, it produces weighted values ​​for each criterion, namely Raw Materials (0.30), Labor (0.32), Capital (0.37). Meanwhile, the weighted value of each alternative is Efficiency in Use of Raw Materials (0.28), Training and Enhancement of Labor (0.32), Efficiency in Use of Capital (0.37), From the results of data processing criteria, for the most important criteria in increasing tofu and tempeh production is the Capital criterion, and for the best priority is Capital Use Efficiency.